Mendelian Randomization Study of Heart Failure and Stroke Subtypes - Li, Quan; Yan, Shijiao; Li, Yan; Kang, Hai; Zhu, Huadong; Lv, Chuanzhu (Frontiers in Cardiovascular Medicine, 2022)
Background: Whether heart failure is independent risk factor of ischemic stroke and hemorrhagic stroke remains controversial. We employed a multivariable Mendelian randomization (MR) to further investigate the causal effects of heart failure on the risk of stroke and stroke subtypes. Methods: Genetically predicted heart failure was selected as instrumental variables from published genome-wide association studies (47,309 cases and 930,014 controls). Association estimates for stroke were obtained from another two genome-wide association studies with 47,309 ischemic stroke and 1,545 intracerebral hemorrhage. The random-effects inverse variance-weighted model was applied as the main method, along with sensitivity analysis. Atrial fbrillation, coronary heart disease and systolic blood pressure were controlled for mediating effects in multivariable Mendelian Randomization. Results: Genetically predicted heart failure was significantly associated with any ischemic stroke (odds ratio [OR], 1.39; 95% confidence interval [CI], 1.12–1.74; p = 0.03), large artery stroke (OR, 1.84; 95% CI, 1.27–2.65; p = 0.001), and cardioembolic stroke (OR, 1.73; 95% CI, 1.21–2.47; p = 0.003), but without small vessel stroke (OR, 1.1; 95% CI, 0.80–1.52; p = 0.56) and intracerebral hemorrhage (OR, 0.86; 95% CI, 0.41–1.83; p = 0.699) in univariable Mendelian Randomization. However, these significant associations were attenuated to the null after adjusting for confounding factor in multivariable Mendelian Randomization. Conclusions: There was no direct causal association between heart failure and stroke in our study. The association between heart failure and ischemic stroke can be driven by atrial fbrillation, coronary heart disease, and systolic blood pressure.